2015
DOI: 10.1017/s1479262115000179
|View full text |Cite
|
Sign up to set email alerts
|

Cross-species amplification and characterization of new microsatellite markers for the macaw palm,Acrocomia aculeata(Arecaceae)

Abstract: Microsatellites or simple sequence repeats (SSRs) are useful molecular markers allowing for efficient conservation and sustainable use of genetic resources of plant species. Development of SSR marker system for new species is a very expensive task and time consuming. Cross-species amplification of microsatellite loci is considered as a cost-effective approach for developing microsatellite markers for new species. The aim of this work was to examine the transferability of some SSR markers of two Arecaceae speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
6
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
4
6
1
1
Order By: Relevance
“…For the entire sample set plants (356 plants, 86 from NP and 270 progenies), the 14 microsatellite loci analysed were polymorphic. This result confirms the polymorphism found with this marker in A. aculeata in previous studies (Bazzo et al, 2018; Lanes et al, 2015, 2016; Mengistu et al, 2016; Nucci et al, 2008). However, at the gSSR loci were more polymorphic than the EST‐SSR (Table 2).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…For the entire sample set plants (356 plants, 86 from NP and 270 progenies), the 14 microsatellite loci analysed were polymorphic. This result confirms the polymorphism found with this marker in A. aculeata in previous studies (Bazzo et al, 2018; Lanes et al, 2015, 2016; Mengistu et al, 2016; Nucci et al, 2008). However, at the gSSR loci were more polymorphic than the EST‐SSR (Table 2).…”
Section: Discussionsupporting
confidence: 91%
“…Another possible explanation is that inbreeding depression is also contributing to the reduction of homozygotes. (Lanes et al, 2015;Mengistu, 2015) and open pollination progenies (Coelho et al, 2018;Lanes et al, 2016). High levels of genetic diversity are expected in species with high outcrossing rates.…”
Section: Genetic Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…They also included studies on the photosynthetic capacity of acrocomia (Pires et al 2013) as well as microbial and chemical changes in soils of acrocomia habitats (Diniz et al 2014). A major advancement in the context of molecular biology was the development of a protocol for DNA extraction from different tissues (Lanes et al 2013) and cross-species amplification of microsatellite markers for A. aculeata (Mengistu et. al.…”
Section: A Short History Of Acrocomia Researchmentioning
confidence: 99%
“…Five of the primers (Aacu07, Aacu10, Aacu12, Aacu26, and Aacu30) were obtained from Nucci et al [5] and three (Aacu38, Aacu45, and Aacu74) identified from Nucci [27]. The other two markers (Aac04 and Aac12) were obtained from sets of SSR makers originally developed for Astrocaryum aculeatum and selected for A. aculeata [28] (Table 2). PCR products were denatured in a bromophenol blue dye solution at 95 • C for 5 min in the thermal cycler just before running in 6% polyacrylamide gel electrophoresis in 1xTBE (Tris-Borate-EDTA, Sigma-Aldrich Corporation, St. Louis, MO, USA) buffer solution at 60 W for 1 h and 40 min.…”
Section: Condition Of Polymerase Chain Reaction (Pcr) and Electrophormentioning
confidence: 99%